Analysing length of stay disparities in inpatient forensic psychiatric care: a cross-sectional study in Czechia - Páv, Marek; Vaníček, Ondřej; Závora, Jiří; Pekara, Jaroslav; Zahrádka-Kȍhlerová, Michaela; Papežová, Simona; Anders, Martin (International journal of mental health systems, 2025)
BACKGROUND: Length of stay (LoS) is a critical parameter of inpatient forensic treatment functioning. Inpatient forensic LoS in Czechia varies across hospitals with the number of patients per 100,000 inhabitants and the treatment duration. We aimed to analyse these inter-hospital differences and provide relevant sociodemographic and treatment-related data. METHODS: We collected descriptive parameters from 841 forensic inpatients from 13 hospitals in Czechia, with follow-up data collection after 6 months (N = 800). Data from eight hospitals with > 50 patients (N = 765) were entered into linear regression analyses with subsequent resampling to identify differences in LoS associated with index offence, diagnosis, and treatment type, thereby highlighting interhospital variations. RESULTS: The cohort comprised predominantly males (mean age, 41.84 years; standard deviation [SD] 3.63) with extended mental health histories; the mean main diagnosis length was 13.2 years (SD 12.18). Most inmates committed violent offences, with psychotic, substance use, or paraphilic disorders predominating. Family contact remained common despite the patients' poor socioeconomic status. The mean LoS was 1,327.58 (SD 1642.41) days. We observed significant differences in LoS among patients from the same diagnostic group. Within the whole system, patients with substance abuse disorders, psychotic disorders, and intellectual disabilities stayed for 760, 1490, and 2441 days, respectively. Violent index offences increased LoS in most hospitals, as did sexual offences, but "other" minor criminal offences (non-violent, non-sexual) were associated with increased LoS only in some hospitals. Sex offender treatment significantly affected LoS in some hospitals, while enrolment into substance use programmes shortened it. CONCLUSIONS: Our study revealed significant inter-hospital variations in LoS associated with index offences, diagnoses, or treatment programs, which could be related to previously unrecognised institutional factors. Regular evaluation of treatment outcomes and implementation of standardised guidelines across the entire system is necessary to balance these differences. The insights provided into inpatient treatment in Czechia can be used to guide policy and practice improvements, enhancing the quality of forensic psychiatric care and ensuring the rights and well-being of the patients. The study addressed the knowledge gap existing in the available literature regarding previously unrecognised factors influencing the LoS at the system "mezzo" level.
Keywords: Czechia; Multicentre study; Forensic psychiatric care; Inpatient forensic treatment; Representative sample; Linear regression analysis; Hospital effect; Forensic length of stay; Mental disorder; Forensic psychiatry